Remarks by World Bank Group President David Malpass at the Sina Finance 2022 ESG Global Leaders’ Summit - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at the Sina Finance 2022 ESG Global Leaders’ Summit on June 28, 2022. He mentioned that in response to Russia’s invasion of Ukraine, countries are shifting their energy policy priorities in ways that may slow down the energy transition and affect global climate goals and the achievement of electricity access. He said that the increased price of natural gas is already causing increased use of coal, diesel, and heavy fuel oil in the developing world. He insisted that it will be important to identify, fund and implement the most impactful projects in terms of GHG emissions and resilience in adapting to major climate vulnerabilities. .He said that to help focus efforts in developing countries, the World Bank Group has launched a new core diagnostic called Country Climate and Development Reports, or CCDRs. He described that constant innovation will be needed as the private sector applies significant funding to global public goods. He highlighted that the World Bank promotes global transparency on climate metrics, targets, and outputs so that we can create opportunities, tackle challenges, and help countries maximize positive outcomes in their climate transition. He mentioned that China’s role as a major global creditor gives it additional responsibility to support the global shift toward investments with high ESG standards. He concluded by saying that a commitment to high standards of transparency and environmental and social risk management, similar to the standards that the World Bank Group and other MDBs follow, would help recipient countries achieve sustainable development while also significantly lowering risks for Chinese investors themselves.